Selecting sorting centres to avoid long distance transport of weaned beef calves - Morel-Journel, T. (Sci Rep, 2021)
The transport of weaned calves from cow–calf producers to fatteners is a general concern for the young bull industry due to its documented negative impact on the welfare, health and performance of the animals. These transfers are often managed by intermediaries who transport weaned calves to sorting centres, where they are grouped into batches before being sent to fattening units. In this study, we present an algorithm to limiting these transfer distances by appropriately selecting the sorting centre through which they must go. We tested the effectiveness of this algorithm on historical data from a French beef producer organization managing 136,892 transfers using 13 sorting centres. The results show a decrease in the transfer distances compared to the historical record, especially for the calves travelling over long distances (− 76 km, i.e. 18% on average for the 33% longest transfers). Moreover, the distribution of calves between the sorting centres proposed by the algorithm reveals differences in their efficiency in minimizing transfer distances. In addition to its usefulness as a management tool for the daily transport of cattle, this algorithm provides prospects for improving the management of the sorting centres themselves.